Unraveling the ecotoxicological effects of micro and nano-plastics on aquatic organisms and human health - Naz, Saima; Chatha, Ahmad Manan Mustafa; Khan, Nisar Ahmed; Ullah, Qudrat; Zaman, Faisal; Qadeer, Abdul; Khan, Ibrar Muhammad; Danabas, Durali; Kiran, Azka; Skalickova, Sylvie; Bernatova, Silvie; Khan, Muhammad Zahoor; et al. (Frontiers in Environmental Science, 2024)
Plastic pollution ranks among the most severe environmental disasters caused by humans, generating millions of tonnes of waste annually. The extensive and unregulated use of plastics has led to ecotoxicity and environmental imbalance.Microplastics (MPs) are prevalent in aquatic environments, and these MPs further degrade into even smaller particles known as nano-plastics (NPs). Both MPs and NPs impact the environment by readily absorbing organic pollutants and pathogens from their surroundings, owing to their bigger surface area to volume ratio. This review focuses on the source of origin, bioaccumulation, and potential impact of MPs and NPs on aquatic organisms and human health.Additionally, the review explores various methods employed for identification and quantification of these particles in aquatic ecosystems. Sufficient information is available on their characteristics, distributions, and effects on marine ecosystems compared with freshwater ecosystems. For plastic particles <10 μm, more toxicological effects were observed compared with larger size particles, in aquatic life. Understanding the mechanism of action and ecotoxicological effects of micro/nano-plastics on the health of aquatic life across various trophic levels, as well as human health, is of utmost importance. We address knowledge gaps and provide insights into future research approaches for a better understanding of the interactive mechanisms between binary pollutants.